2016
DOI: 10.1016/j.aquaculture.2015.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Biofloc contribution to antioxidant defence status, lipid nutrition and reproductive performance of broodstock of the shrimp Litopenaeus stylirostris: Consequences for the quality of eggs and larvae

Abstract: The aim of this study was to determine biofloc contributions to the antioxidant status and lipid nutrition of broodstock of Litopenaeus stylirostris in relationship with their reproductive performance and the health of larvae produced. Shrimp broodstock reared with Biofloc technology (BFT) compared to Clear water (CW) exhibited a higher health status with (i) a better final survival rate during the reproduction period (52.6% in CW against 79.8% in BFT); (ii) higher glutathione level (GSH) and total antioxidant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(29 citation statements)
references
References 58 publications
0
26
0
3
Order By: Relevance
“…Maturation diet of shrimp in captivity has been traditionally based on the female gonad macronutrient composition (Middleditch et al, 1979), but there are several micronutrients that shrimp use during maturation and that are less known. Here, we found that pond-reared shrimp fed Ulva also have reduced (Kent, Browdy, & Leffler, 2011;Varadharajan & Pushparajan, 2013) and when fed biofloc they have a better antioxidant defence status (Cardona et al, 2016). Shrimp even preferred and ingested more plant material (filamentous green algae, diatoms, cyanobacteria) over pellets and animal remains, including exuvia (Focken, Groth, Coloso, & Becker, 1998).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Maturation diet of shrimp in captivity has been traditionally based on the female gonad macronutrient composition (Middleditch et al, 1979), but there are several micronutrients that shrimp use during maturation and that are less known. Here, we found that pond-reared shrimp fed Ulva also have reduced (Kent, Browdy, & Leffler, 2011;Varadharajan & Pushparajan, 2013) and when fed biofloc they have a better antioxidant defence status (Cardona et al, 2016). Shrimp even preferred and ingested more plant material (filamentous green algae, diatoms, cyanobacteria) over pellets and animal remains, including exuvia (Focken, Groth, Coloso, & Becker, 1998).…”
Section: Discussionmentioning
confidence: 75%
“…Shrimp fed biofloc (aggregation of bacteria, microalgae, protozoa, etc.) are able to actively ingest and digest microalgae in suspension (Kent, Browdy, & Leffler, ; Varadharajan & Pushparajan, ) and when fed biofloc they have a better antioxidant defence status (Cardona et al, ). Shrimp even preferred and ingested more plant material (filamentous green algae, diatoms, cyanobacteria) over pellets and animal remains, including exuvia (Focken, Groth, Coloso, & Becker, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Regunathan, ). However, the biofloc technology could be seen as a pre‐maturation system where animals obtain benefits of the nutritive biofloc particles improving its nutritional history (Cardona et al., ; Chim et al., ; Emerenciano et al., ). In fact, the benefits obtained from biofloc in grow‐out or pre‐maturation appear to persist in the broodstock and hence in the progeny (Emerenciano, Cuzon, et al.…”
Section: Discussionmentioning
confidence: 99%
“…As an effect of the nutritional history and natural selection, wild shrimp broodstock have better reproductive performance than domesticated shrimp (Braga, Lopes, Krummenauer, Poersch, & Wasielesky, 2011;Regunathan, 2008). However, the biofloc technology could be seen as a prematuration system where animals obtain benefits of the nutritive biofloc particles improving its nutritional history (Cardona et al, 2016;Chim et al, 2014;Emerenciano et al, 2014). In fact, the benefits obtained from biofloc in grow-out or pre-maturation appear to persist in the broodstock and hence in the progeny Emerenciano, Cuzon, Arevalo, et al 2013).…”
Section: Reproductive Performance and Contribution Of Food Sources mentioning
confidence: 99%